Effects of Rotifers Enriched With Different Enhancement Products on Larval Performance and Jaw Deformity of Golden Pompano Larvae Trachinotus ovatus (Linnaeus, 1758) - Fu, Zhengyi; Yang, Rui; Zhou, Shengjie; Ma, Zhenhua; Zhang, Tao (Frontiers in Marine Science, 2021)
This study evaluated the effects of rotifers enriched with three enhancement products (Nannochloropsis, S.presso and Algamac 3080)on the body fatty acid composition, growth, survival, jaw deformity, and bone development-related gene expression of the golden pompano larvae in first feeding. The rotifers enriched with Nannochloropsis were rich in EPA, and the rotifers enriched with S.presso and Algamac 3080 were rich in DHA and the level of DHA in Algamac 3080 is higher than that in S.presso. The first feeding started at 3 DPH and data were collected at 8 DPH. The results showed that the body fatty acid composition of the larvae was basically the same as that of the feeding rotifers. The specific growth rate of S.presso and Algamac 3080 treatment were significantly higher than un-enriched treatment (P < 0.05). The survival rate of Algamac 3080 treatment was significantly lower than other treatments (P < 0.05), and the jaw deformity rate of S.presso treatment was significantly lower than Nannochloropsis and un-enriched treatment (P < 0.05). The expression level of BMP2 and BMP4 in golden pompano larvae were not significantly affected by the enhancement products (P > 0.05), and the expression level of RXRα decreased significantly in the S.presso and Algamac 3080 treatment (P < 0.05). This study indicates that S.presso was an enhancement product more suitable for rotifers for golden pompano larvae first feeding. This study provided reliable reference and guidance for the first feeding of golden pompano larvae, and also provided more reference data for the study of the mechanism of diet on larval fish bone deformity.